Emerging Role of Migration and Invasion Enhancer 1 (MIEN1) in Cancer Progression and Metastasis - Kushwaha, Prem Prakash; Gupta, Sanjay; Singh, Atul Kumar; Kumar, Shashank (Frontiers in Oncology, 2019)
Tumor metastasis is a sequential event accounting for numerous cancer-related fatalities worldwide. The process of metastasis serially involves invasion, intravasation, extravasation and tumor growth at the secondary site. Migration and invasion enhancer 1 (MIEN1) is a membrane associated protein overexpressed in various human cancers. Biological activity of MIEN1 is driven by geranylgeranyltransferase-I mediated prenylation at CAAX motif and methylation of the prenylated protein that anchors MIEN1 into the cellular membrane. Post-translationally modified MIEN1 interacts with Syk kinase and Annexin A2 protein; polymerizes G-actin and stabilizes F-actin filament; induces focal adhesion kinase phosphorylation and decrease cofilin phosphorylation implicated in both invasion and metastasis of different cancer types. In the present review, we discuss the structure, function, and involvement of MIEN1 in cancer progression. We also highlight the future prospects of MIEN1 as an emerging molecule and novel target in cancer cell invasion and metastasis.